Economics of different treatment options of benign prostatic hyperplasia in Turkey - (:unkn) unknown (Kluwer Academic Publishers, 1996)
Benign prostatic hyperplasia (BPH) has an important impact on the national health economics and can be managed in a large spectrum of modalities from simple follow-up to surgery. In this study, we aimed to compare different treatment options of BPH in terms of cost effectiveness in Turkey. The first evaluation of a BPH patient has a cost of $200. The cost of TURP or open prostatectomy (OP) in our hospital including all the expenses is $740. Finasteride has an annual cost nearly equal to TURP and OP. Considering the expenses of the close follow-up studies and regular visits, one-year lasting Finasteride treatment is two times more expensive than surgery. In comparison with medical treatment options, TURP as the gold standard of treatment of BPH is cost effective when long-term expenses are considered.